Must we measure what we mean? - Hansen, Nat (Inquiry (Oslo), 2017)
This paper excavates a debate concerning the claims of ordinary language philosophers that took place during the middle of the last century. The debate centers on the status of statements about 'what we say'. On one side of the debate, critics of ordinary language philosophy argued that statements about 'what we say' should be evaluated as empirical observations about how people do in fact speak, on a par with claims made in the language sciences. By that standard, ordinary language philosophers were not entitled to the claims that they made about what we would say about various topics. On the other side of the debate, defenders of the methods of ordinary language philosophy sought to explain how philosophers can be entitled to statements about what we would say without engaging in extensive observations of how people do in fact use language. In this paper, I defend the idea that entitlement to claims about what we say can be had in a way that doesn't require empirical observation, and I argue that ordinary language philosophers are (at least sometimes) engaged in a different project than linguists or empirically minded philosophers of language, which is subject to different conditions of success.